Darurah Typology in Contemporary Health Sciences - Makki, Achmad; Umar, Hasbi; Ulum, Bahrul (Yayasan Sembilan Pemuda Indonesia, 2023)
As the current advancement of health technology nears completion, so does the desire to discuss and learn about it. Scientists from both Islamic and non-Islamic scientific groups are discussing and even participating in its development. The advancement of health technology, which is valued by almost the entire world's population, necessitates a review of its benefits and drawbacks, including Islamic academics who see this necessity in terms of its relevance to aspects of Islamic law. According to academics, Islamic law in relation to technological developments is dynamic. It is subject to change due to its distinct nature from the source of law. Sources of law are qat'i (static), whereas legal products derived from these sources of law are zanni (dynamic); ensure change. The bizarre potential of this law is then used to trace all kinds of events, both old and new, particularly those concerning the advancement of contemporary health sciences.